Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae) - Evenhuis, Neal L.; Gang, Yao (Zootaxa, 2016)
The bee fly genus Euchariomyia Bigot is reviewed and new records from the Oriental Region are given. Five names (for four species-level taxa) have been associated with species in the genus. Examinations of types, as well as homotypic and topotypic specimens, shows all five names to belong to a highly variable single species, Euchariomyia dives Bigot. The following species are here shown to be the same as Euchariomyia dives Bigot: Bombylius pulchellus Wulp, 1880, Bombylius scintillans Brunetti, 1909, and Bombylius brunettii Senior-White, 1922, n. syn. The genus is known primarily from the southern and eastern Oriental Region and ranges into the Palaearctic in eastern China. We extend the distribution of the genus with new records in the southeastern Oriental Region [Indonesia (Sumatra), Laos, Peninsular Malaysia, and Vietnam].